2021
DOI: 10.2147/jir.s322875
|View full text |Cite
|
Sign up to set email alerts
|

Necroptosis Underlies Neutrophilic Inflammation Associated with the Chronic Rhinosinusitis with Nasal Polyps (CRSwNP)

Abstract: Background Necroptosis is an inflammatory cell death associated with a variety of chronic diseases. Chronic rhinosinusitis with nasal polyps (CRSwNP) is a chronic inflammatory disease accompanied by eosinophil and neutrophil infiltration. The role of necroptosis in the pathogenesis of CRSwNP remains elusive. Methods Cell death, including apoptosis, pyroptosis and necroptosis in control sinonasal mucosa and CRSwNP, were analyzed by immunoblotting, immunohistochemistry (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…Studies conducted on Danish and Pennsylvanian populations, also found a male predominance in CRSwNP and the male to female ratio ranged between 1.3 and 2.2. [1][2][3]6 Nasal polyposis is considered to be grouped into eosinophilic and non-eosinophilic types, but among various attempts to further divide the nasal polyps based on inflammatory cells, in one of the subdivisions they can be clustered into five types depending on the presence and predominance of lymphocytes, plasma cells, eosinophils, neutrophils, and mixed inflammatory cells. 3,5,7 This pattern of results about the diverse distribution of type and population of the inflammatory cell can be explained as, sinonasal polyposis, commonly also known as Chronic Rhinosinusitis with Nasal Polyps, i.e., CRSwNP, is characteristically a heterogeneous disease with several etiologies and multiple predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies conducted on Danish and Pennsylvanian populations, also found a male predominance in CRSwNP and the male to female ratio ranged between 1.3 and 2.2. [1][2][3]6 Nasal polyposis is considered to be grouped into eosinophilic and non-eosinophilic types, but among various attempts to further divide the nasal polyps based on inflammatory cells, in one of the subdivisions they can be clustered into five types depending on the presence and predominance of lymphocytes, plasma cells, eosinophils, neutrophils, and mixed inflammatory cells. 3,5,7 This pattern of results about the diverse distribution of type and population of the inflammatory cell can be explained as, sinonasal polyposis, commonly also known as Chronic Rhinosinusitis with Nasal Polyps, i.e., CRSwNP, is characteristically a heterogeneous disease with several etiologies and multiple predisposing factors.…”
Section: Discussionmentioning
confidence: 99%
“…This type of inflammation is predominant in the Asian population having CRS w Nasal polyposis. 2,3,9 However, the studied population is predominantly of the Mongolian race of Asian counties. In the Aryan race like the Indian population, the Th2 is more predominant than Th17.…”
Section: Neutrophilmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic sinusitis, insufficient IFN-γ-induced autophagy can lead to the p62-dependent apoptosis of epithelial cells, while TNF-α and IFN-γ-induced necroptosis may promote the production and release of numerous pro-inflammatory cytokines and lead to neutrophil infiltration to exacerbate inflammation in CRSwNP [ 293 , 294 ]. SEB can also stimulate IL-21 expression, and IL-21 can also induce Th17 differentiation [ 89 , 90 ].…”
Section: Basic Types Of Diseases Caused By S Aureus ...mentioning
confidence: 99%
“…The role of epithelial cells in the pathogenesis of CRS has attracted more and more attention. As the first natural barrier to contact external stimuli and an important structure of innate immunity, epithelial cells on the surface of nasal mucosa play an important role in protecting the body from external harmful factors [10][11][12] . Once the epithelial cell barrier function is damaged, it is mainly manifested in epithelial cell abscission and dysfunction in CRS, which will provide conditions for the invasion of external harmful substances, such as bacteria, virus invasion and allergen exposure, so as to cause and aggravate the chronic inflammation of nasal cavity and paranasal sinus mucus membrane and lead to the accumulation of inflammatory cells and inflammatory factors [13,14] .…”
mentioning
confidence: 99%